Dvojezična vzgoja in izobraževanje - Novak-Lukanovič, Sonja (Razprave in gradivo - Inštitut za narodnostna vprašanja (1990), 1993)
The paper deals with different individual viewpoints regarding bilingual education and the role of minority language within. We were interested in respondents' views concerning the present model of bilingual education that isbeing implemented in the ethnically mixed area of Prekmurje.
Keywords: dvojezičnost; izobraževanje; Madžari; narodne manjšine; Prekmurje; Slovenija; šolstvo